Demographic Assessment of the Sustainability of Small and Medium-sized Cities in the Russian North - Fauzer, Viktor V.; Smirnov, Andrey V.; Fauzer, Galina N. (Economy of Regions, 2021)
Since the dissolution of the USSR and advent of market relations, small and medium-sized Russian cities have experienced many economic and social problems due to their peripheral status. At the same time, they form the main framework for the settlement of the northern territories. The research aims to reveal the importance of small and medium-sized cities in the settlement system of 13 regions of the Russian North by studying their demographic dynamics. We examined the hypothesis that the demographic sustainability of these cities depends on the time of their formation. A proposed methodology for assessing the demographic sustainability of cities is based on five groups: demographically sustainable, relatively sustainable, unsustainable, critically unsustainable, instability. Four periods of the formation of small and medium-sized cities are defined: colonisation of the Russian North (1584-1917); industrialisation and urbanisation of the northern territories (1918-1959); from coercion to encouragement - northern romance (1960-1989); from settlement to abandonment - depopulation (1990-2020). For each period, the cities were assessed in terms of their demographic sustainability. The current sustainability of the cities was shown to be dependent on the period of their formation. Compared with the rest of Russia, the structure of settlements in the North revealed both similarities (concentration of the population in large cities) and differences (the proportion of the population living in small and medium-sized cities is higher, but lower in rural areas). Future research will focus on developing a methodology for assessing the «saturation» of small and medium-sized cities in the Russian North.